Low- and high-frequency transcutaneous electrical nerve stimulation have no deleterious or teratogenic effects on pregnant mice. Issue 2 (June 2015) - Yokoyama, L.M.; Pires, L.A.; Ferreira, E.A. Gonçalves; Casarotto, R.A.
Abstract: Objective: To evaluate the effects of application of transcutaneous electrical nerve stimulation (TENS) at low and high frequencies to the abdomens of Swiss mice throughout pregnancy. Design: Experimental animal study. Setting: Research laboratory. Participants: Thirty Swiss mice received TENS throughout pregnancy. They were divided into three groups ( n = 10): placebo, low-frequency TENS (LF group) and high-frequency TENS (HF group). Interventions: In the placebo group, the electrodes were applied to the abdominal region without any electrical current. In the LF group, the frequency was 10 Hz, pulse duration was 200 μs and intensity started at 2 mA. In the HF group, the same parameters were applied and the frequency was 150 Hz. All stimulation protocols were applied for 20 min/day from Day 0 until Day 20. Main outcome measures: The pregnant mice were weighed on Days 0, 7, 14 and 20 to verify weekly weight gain by two-way analysis of variance. The numbers of fetuses, placentas, implantations, resorptions and major external fetal malformations on Day 20 were analysed using the Kruskal–Wallis test. Results: No significant differences were found between the placebo and TENS groups ( P > 0.05). Conclusion: Application of low- and high-frequency TENS to the abdomens of pregnant mice did not cause any deleterious or major teratogenic effects.